Utilization of Small-dimension Stock in the Building Industry Through Modern Timber Engineering - Masani, N. J.; Seth, S. K. (Indian Forester, 1959)
The scope for utilizing small-dimension stock instead of large timber pieces, to construct (with the aid of modern timber engineering techniques) timber structures used in the building industry is indicated. The effects of such chang-eover, not only on timber conversion and utilization, but also on the objects and methods of forest management are explained. It is suggested that fast-grown timber species could be raised and worked with advantage on comparatively short rotations, in conjunction with the utilization of small-dimension stock for constructional work.